(3GdbjGOI h UfY GdJGQjNs - (3eMeO YHO GdYRjR(B, (3QHjYs ((3YeGf(B:s (3OQhH ddfTQ(B,s, 2010)
(3GdbGOI h GdJGQjN , GdbjGOGJ GdJGQjNjI h GdbjGOGJ GdUOaI, GdbjGOI GdaQOjI h GdbjGOI GdeDSSjI , eUGO Q GdTQYjI GdSjGSjI , GdOjebQGWjI h GdbjGOI GdSjGSjI , GdQFjS HhT h GdQFGSI GdCeQjcjI ,GdNha h SjGSI GdJNhja , KbGaI GdNha h GdMQH Ydi GdGQgGH , YHbQjI GdaTd , GdEjOjhdhLjG h YHbQjI GdaTd , GdJWhQ GdJGQNj ddYedjGJ GdeLJeYjI , GdYedjGJ GdeLJeYjI h UfY GdJGQjN , GdfgL GdJGQjNj ddJWhQ GdeLJeYj , GdacQI GdEjOjhdhLjI h GdCReGJ GdeLJeYjI ,HOGjI GdMQH h fgGjI GdSdGe , eSJbHd GdbjGOI GdJGQjNjI , GdbjGOI GdSjGSjI hQhM GdYUQ (B.s
Keywords: (3GdJGQjNs; (3GdbjGOIs; (3GdbjGOI GdSjGSjIs; (3GdbjGOI(B- (3GdJGQjNjIs